2015
DOI: 10.1002/nau.22936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous positive airway pressure on nocturnal urine production in patients with obstructive sleep apnea syndrome

Abstract: CPAP treatment decreases night-time urinary frequency by reducing nocturnal urine production and improves QOL in patients with OSAS. Neurourol. Urodynam. 36:376-379, 2017. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
2
30
0
8
Order By: Relevance
“…22 Correspondingly, treatment of OSA with continuous positive airway pressure (CPAP) has been shown to reduce nocturia. 23 OSA has also been linked to other OAB symptoms such as urgency. 4,5,24 This suggests that the urological effects of OSA may extend beyond nocturnal polyuria, involving such mechanisms as OSA-induced hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…22 Correspondingly, treatment of OSA with continuous positive airway pressure (CPAP) has been shown to reduce nocturia. 23 OSA has also been linked to other OAB symptoms such as urgency. 4,5,24 This suggests that the urological effects of OSA may extend beyond nocturnal polyuria, involving such mechanisms as OSA-induced hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of nocturia in patients with OSAS may be associated with excessive urine production and hormonal imbalance during the night time. Some studies have demonstrated that continuous positive airway pressure can improve nocturia symptoms in patients with obstructive sleep apnea syndrome …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that continuous positive airway pressure can improve nocturia symptoms in patients with obstructive sleep apnea syndrome. 14,15 The first-line pharmacotherapy for OAB starts with antimuscarinics or mirabegron. 16,17 These oral therapies are not sufficiently effective for many patients.…”
Section: Introductionmentioning
confidence: 99%
“…ANP increases renal sodium and water excretion. Nighttime awakenings and subsequent trips to the bathroom can thus be reduced by applying continuous positive airway pressure (CPAP) …”
Section: Nocturnal Polyuriamentioning
confidence: 99%
“…Nighttime awakenings and subsequent trips to the bathroom can thus be reduced by applying continuous positive airway pressure (CPAP). [22][23][24][25] In patients with excessive fluid intake at night, nocturia can be improved by reducing fluid intake 4-6 hours prior to bedtime and limiting consumption of caffeinated products during the evening. 18 In patients with lower extremity oedema secondary to CHF or poor peripheral circulation, stockings and leg elevation may help to reduce the need to void during sleep.…”
Section: Noc Turnal P Oly Uriamentioning
confidence: 99%